Analisis Ketepatan Penetapan Kawasan Andalan (Studi Kasus di Jawa Tengah 2000 – 2005) - Sri Mulyani; Herman Sambodo; Lilis Siti Badriah (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2008)
The purpose of this research is to analyze the pattern and structure growth of economic in Central Java province both for staying in mainstay area and not mainstay area, to identifydominant sectors of districst/cities in Central Java Province both of that area, to analyze the regional specialization between that area and to analyze accuracy suitable assessment of mainstay area determination in Central Java Province. The object of this research is districts/cities in Central Java Province, using data on 2000-2005. The data are Gross Domestic Regional Product (GDRP) at constant prices of 2000 and population. The source of data is its Central Bureau of Statistic. The analysis methods that used are Location Quotient (LQ) Model, Klassen Thypology, Regional Specialization Index, and Logit Model. The results of research indicate that there are 5 of 22 districts/cities in mainstay area including go forward and grow quickly area category (Cilacap, Karanganyar, Kudus, Kota Semarang, Kota Surakarta), 5 district/cities including go forward quickly but depressed area category, 5 districts/cities including expand quickly category, dan 8 area including to be neglected relatively area category. Otherwise, area that is not mainstay area divide to two area categories, 2 districts/cities including go forward quickly but depressed area category and 11 districts/cities including to be neglected relatively area category. All of districts/cities in mainstay and not mainstay area have a variety of dominant sectors. Determinanation of mainstay area policy just consider economic growth and income percapita without consider regional specialization Key words: mainstay area, economic growth, dominant sectors, regional specialization index.